One China Policy sebagai Upaya China Menuju Kekuatan Global di Kawasan Indo-Pasifik - Muhammad Fathir Furqan; Darwis Darwis; Imam Fadhil Nugraha (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
China first established its mission to become a superpower in the year 2000, when they began implementing an open-ended trading system, where they implemented all of that in order to be able to equal or exceed the power of the United States in the coming years, one way is by expanding its influence in the Indo-Pacific region, where the region is one of the world's trading centers, in which the country of China stands, so that China can launch its mission more easily. Working with ASEAN and the South Pacific countries, developing trade cooperation, and providing support to specific countries for economic development are some of their methods. The "One China Policy" is one of the initiatives that the South Pacific nations have adopted as a result of their collaboration. About the study of such topics, the research techniques that the author employed in this study are descriptive techniques that make use of secondary data sources as a type of data. When examining China's aspirations to become a superpower through the perspective of realism and the theory of the balance of power, it can be concluded that, despite certain dynamics brought about by disputes in the South and East China Seas, they has succeeded in doing so, especially in the Indo-Pacific region.